Effect of computed tomography scanner location on time‐to‐computed tomography in the emergency department: A before and after study. (16th November 2021) - Cabilan, CJ; Eley, Robert; Staib, Andrew; Rowney, Ben; Kay, Phillip
Abstract: Objectives: To compare time metrics associated with a temporary disruption to ED computed tomography (CT) scanner location from adjacent to the ED with direct access from resuscitation rooms, to a location remote to the ED. Methods: A retrospective before and after study was conducted in a public metropolitan ED with over 66 000 presentations annually. Time‐to‐CT metrics, operational time metrics and ED length of stay were extracted and analysed from presentations between October 2020 and January 2021. Results: There were 3031 CT scans during the study period. Overall, the disruption was associated with a significant 27–36 min delay ( P  < 0.01) in time‐to‐CT start; these delays were also observed in a subset of trauma patients. In a subset of presumed stroke patients, time‐to‐brain perfusion was significantly delayed by up to 10 min ( P  < 0.01). There was a 14% ( P  < 0.01) greater demand for operational services and a time imposition of up to 8 min ( P  < 0.01) to transport patients to or from CT scanning when the CT scanner was located away from the ED. ED length of stay was consistent at all time points. Conclusion: Although rapid, proximate access to CT scanning is often considered desirable in terms of the management of trauma and other time‐critical emergencies, the wider time and resource implications demonstrated in this study suggest a potential broader benefit to co‐located CT scanning in ED. Our experience could be considered in future re‐design of EDs. Abstract : Computed tomography (CT) location is an overlooked factor contributing to the timeliness of CT imaging. In this study, we compared time and resource implications between two conditions: CT scanner adjacent to the ED with direct access from resuscitation rooms, and CT scanner outside the ED. Results showed that when CT scanners were located outside the ED, median time‐to‐CT increased by up to 37 min, and demands for operational services increased.